Coherence of pregnancy planning within couples expecting a child. Issue 10 (October 2015) - Bodin, Maja; Stern, Jenny; Käll, Lisa Folkmarson; Tydén, Tanja; Larsson, Margareta
Abstract Background joint planning and decision-making within couples have evident effects on the well-being of the family. The purpose of this study was to investigate the level of pregnancy planning among pregnant women and their partners and to compare the coherence of pregnancy planning within the couples. Methods pregnant women and their partners were recruited from 18 antenatal clinics in seven Swedish counties between October 2011 and April 2012. Participants, 232 pregnant women and 144 partners, filled out a questionnaire with questions about pregnancy planning, lifestyle and relationship satisfaction. 136 couples were identified and the women׳s and partners׳ answers were compared. Results more than 75% of the pregnancies were very or rather planned and almost all participants had agreed with their partner to become pregnant. There was no significant difference in level of pregnancy planning between women and partners, and coherence within couples was strong. Level of planning was not affected by individual socio-demographic variables. Furthermore, 98 % of women and 94 % of partners had non-distressed relationships. Conclusion one of the most interesting results was the strong coherence between partners concerning their pregnancy and relationship. Approaching these results from a social constructivist perspective brings to light an importance of togetherness and how a sense and impression of unity within a couple might be constructed in different ways. As implications for practice, midwives and other professionals counselling persons in fertile age should enquire about and emphasise the benefits of equality and mutual pregnancy planning for both women and men.